Telework Implementation Toward Virtual Organization In Malaysia. - Karia, Noorliza; Asaari, Muhammad Hasmi Abu Hassan (Universiti Sains Malaysia, 2006)
Being a virtual organization is the ultimate achievement for some organizations. As the mammoth step, organizations in the country need to explore the possibilities of accepting and implementing their move in telework and subsequently to turn the organization into a virtual working environment.